Intestinal inflammation and activation of sensory nerve pathways: a functional and morphological study in the nematode infected rat. Issue 6 (1st December 2001) - De Giorgio, R; Barbara, G; Blennerhassett, P; Wang, L; Stanghellini, V; Corinaldesi, R; Collins, S M; Tougas, G
Abstract : BACKGROUND: In the rat, gastric distension elicits an intensity dependent pseudoaffective bradycardia mediated via capsaicin sensitive afferent and cholinergic efferent vagal pathways. Inflammation alters visceral perception although the mediators responsible have not been identified. In the nematode infected rat, there is a substantial increase in neuronal substance P (SP) content of the gut. AIMS: To examine the effects of inflammation on perception of a noxious visceral stimulus and on SP and neurokinin 1 (NK-1) receptor immunoreactivity (IR) in visceral afferent pathways. METHODS: Immunohistochemistry was performed on sections from the jejunum, dorsal root ganglia (DRG), and spinal cord (T1–L1) using SP and NK-1 rabbit polyclonal antibodies. In the DRG, the number of SP-IR or NK-1-IR neurones per section was visually quantified. The pseudoaffective cardiac reflex response to gastric stimulation was compared in control and Trichinella spiralis infected rats. RESULTS: Intestinal inflammation induced a rightward shift in the intensity dependent bradycardic response to gastric distension. This was associated with a marked increase in SP-IR not only in the gut wall but also in the DRG and dorsal horn of the spine. In contrast, NK-1-IR was not increased in the gut wall. Moreover, inflammation evoked a decrease in NK-1-IR in the dorsal horn. No NK-1-IR was identified in the DRG of either control or infected animals. CONCLUSIONS: Intestinal inflammation modulates the capsaicin sensitive pseudoaffective autonomic response to gastric distension, increases SP-IR in afferent pathways, and downregulates dorsal horn NK-1-IR. As the pseudoaffective response is capsaicin sensitive, the rightward shift of the response is likely the consequence of the decrease in NK-1 receptors in the sensory pathways.